Leadership IQ of Singapore undergraduates. - Chia, Queenie. (2008)
This paper presents the findings of a study to identify a reliable tool that could be used to identify the traits and leadership characteristics that are hypothesized in the psychological infrastructure aspect of the Thought Leadership Model, which is proposed by Chan, 2000.